Transformational Leadership Practices and Work Engagement among School Heads: An Explanatory-Sequential Mixed Method Inquiry - Panunciar, Cesar Ryan; Madrigal, Dennis; Bual, Joel (Technium Social Sciences Journal, 2024)
This study examined the transformational leadership and work engagement of 169 public school heads. It also sought an in-depth explanation of their transformational leadership and work engagement experiences. The sample was stratified, and the multifactor leadership questionnaire and Utrecht work engagement scale were used. Semi-structured interviews collected the qualitative data. In selecting 10 participants, maximum variation was employed. Generally, the school heads’ transformational leadership was great, and administrative experience correlated with it. Meanwhile, they had a very great work engagement. Their transformational leadership was associated with their work engagement. The qualitative phase generated four themes: values at the heart of a transformational leader; experience at the heart of shaping transformational leadership knowledge and skills; passion at the heart of a transformational leader; and organizational change and accomplishments mirror the influence of school heads’ transformational leadership to work engagement. As a result, they transformed their organizations and achieved success. Their leadership style stimulated motivation, consideration, idealized influence, and intellectual stimulation among teachers. They have found fulfillment through work. Therefore, transformational leadership and work engagement are vital to a successful organization.